The molecular mechanism of hydrogen bond formation between t-a base pairs within a promoter and a sigma factor - Kurchii, B.A. (Фактори експериментальної еволюції організмів, 2009)
In this report it is described the molecular mechanisms of a promoter (a gene lock) and a
sigma factor (a gene key) interaction during transcription reaction. The hydrogen bond is
formed between the hydrogen at N6 of the adenine and the oxygen at C2 of the thymine. This
process leads to the separation of doubled strands of DNA in the gene lock into two single
strands of DNA and transcription initiation. В цьому повідомленні описуються молекулярні механізми взаємодії промотора (генний
замок) и сигма фактора (генний ключ) в реакції транскрипції. Водневий зв'язок
утворюється між воднем при N6 аденіна и киснем при С2 тиміна. Цей процесс визиває
розходження подвійної нитки ДНК в генному замку на дві окремі нитки ДНК і
ініціацію транскрипції. В этом сообщении описаны молекулярные механизмы взаимодействия промотора
(генный замок) и сигма фактора (генный ключ) в реакции транскрипции. Водородная
связь образуется между водородом при N6 аденина и кислородом при С2 тимина. Этот
процесс ведет к разделению двойной нити ДНК в генном замке на две отдельные нити
ДНК и инициации транскрипции.